Path Planning Robot Using Proximity Sensor - ‘Ain Amirrudin, Nurul; Zhen Mao, Lim (International Journal of Engineering and Technology, 2019)
Automated robots are now commonly used in all places, from automatic production in manufacturing sites to storage arranging robots. Automated robots play an important role in our daily life. These robots may be moving in static or dynamic environment. Hence path planning has to be introduced to help robot find path while avoiding obstacles. In this research, a proximity sensor robot is modelled and simulated.Â The model of the robot is built and simulated in Virtual Robot Experimentation Platform (V-REP) software. A dynamic and static environment is constructed for the robot to be tested where it has to reach the end position from the start position. In static environment, all obstacles are static while dynamic environment the obstacles are movable.Â The performance of the proximity sensor robot is analysed in terms of the angular velocity of the robot, and the time comparison with previous research in static environment and dynamic environment. The results show that the average time taken by the proximity sensor robot is shorter than the previous research.Â Â Â